(untitled) (Homoeopathy for All, 2024)
The time of teething varies from child to child, but it usually starts from 6 months to 12 months of age. Teething is the process by which an infant’s teeth erupt, or break through, the gums. Teething is also referred to as “cutting” of the teeth. Homoeopathy has been found to be very successful in treating dentition problems in children’s and medicines are perfectly safe. A homoeopathic teething remedy includes medicines that ease the symptoms like irritability and swelling in teething toddlers. Homoeopathic medicines also helps baby calm down and get to sleep.